Targeting resources efficiently and justifiably by combining causal machine learning and theory - Gur Ali, Ozden (Frontiers in Artificial Intelligence, 2022)
Efficient allocation of limited resources relies on accurate estimates of potential incremental benefits for each candidate. These heterogeneous treatment effects (HTE) can be estimated with properly specified theory-driven models and observational data that contains all confounders. Using causal machine learning to estimate HTE from big data offers higher benefits with limited resources by identifying additional heterogeneity dimensions and fitting arbitrary functional forms and interactions, but decisions based on black-box models are not justifiable. Our solution is designed to increase resource allocation efficiency, enhance understanding of the treatment effects, and increase acceptance of the resulting decisions with a rationale that is in line with existing theory. The case study identifies the right individuals to incentivize for increasing their physical activity to maximize the population health benefits due to reduced diabetes and heart disease prevalence. We leverage large scale data from multi-wave nationally representative health surveys and theory from published global meta-analysis results. We train causal machine learning ensembles, extract the heterogeneity dimensions of the treatment effect, sign and monotonicity of its moderators with explainable AI; and incorporate them into the theory-driven model with our generalized linear model with qualitative constraints (GLM_QC) method. The results show that the proposed methodology improves the expected health benefits for diabetes by 11% and for heart disease by 9% compared to the traditional approach of using the model specification from the literature and estimating the model with large scale data. Qualitative constraints not only prevent counter-intuitive effects but also improve achieved benefits by regularizing the model.